Resistance to Acetaminophen Interference in a Novel Continuous Glucose Monitoring System. (March 2018) - Calhoun, Peter; Johnson, Terri Kang; Hughes, Jonathan; Price, David; Balo, Andrew K.
Acetaminophen (APAP) can cause erroneously high readings in real-time continuous glucose monitoring (rtCGM) systems. APAP-associated bias in an investigational rtCGM system (G6) was evaluated by taking the difference in glucose measurements between rtCGM and YSI from 1 hour before to 6 hours after a 1-g oral APAP dose in 66 subjects with type 1 or type 2 diabetes. The interference effect was defined as the average post-dose (30-90 minutes) bias minus the average baseline bias for each subject. The clinically meaningful interference effect was defined as 10 mg/dL. The G6 system's overall mean (±SD) interference effect was 3.1 ± 4.8 mg/dL (one-sided upper 95% CI = 4.1 mg/dL), significantly lower than 10 mg/dL. The G6 system's resistance to APAP interference should provide reassurance to those using the drug.